The Books of the Maccabees: Literary, Historical, and Religious Perspectives, by Jan Willem van Henten, ed. - Coşkun, Altay; Scolnic, Benjamin (Journal for the Study of Judaism, 2026)
Keywords: General; Jewish Studies; dept.jst

Adrastus [‘No Escape’]: An Oracle Chain and the Fate of Croesus - Scolnic, Benjamin (Acta Antiqua Academiae Scientiarum Hungaricae, 2026)
Croesus famously consulted oracles to determine whether to make war on Persia in 547/46 BCE. But Herodotus tells us he misunderstood the oracular response, due to a mix of hubris and fate. And yet, was this the oracle that brought doom to the Lydian Empire? The defeat of Croesus is not just the affirmation of the divine knowledge of the Delphic oracle because the king does not interpret the oracle correctly. Rather, his defeat is the affirmation of the divine knowledge of the oracle over the course of the history of his dynasty. From the opposite perspective, we can ask not only why Croesus lost, but why Cyrus won. His victory is based, according to other sources, on a different divine oracle that has nothing to do with Croesus or the dynasty of the Mermnadai. The goal of all these oracles and prophecies will be the return and rise of the legitimate rulers of the world; these oracles not only predict the future over long spans of time but are the overarching cause for the history that unfolds.
Keywords: Croesus; Delphic Oracle; Herodotus; dept.jst; dynastic succession; prophecy

Karomemphitai. Origin stories of Karians in Egypt and their role in the rise of the Saite dynasty - Scolnic, Benjamin (Acta Antiqua Academiae Scientiarum Hungaricae, 2025)
Keywords: Archaeomagnetic dating; Context (archaeology); Foundation (evidence); Karians; Memphis; Power (physics); Saite dynasty; assimilation; dept.jst; identity; oracles

The Oil That Lasted a Thousand Years - Scolnic, Benjamin (Zutot, 2024)
Abstract While the familiar Hanukkah story of the ‘miracle of the oil’ is often dismissed as quaint and fanciful, it may be seen as a final link in an interesting chain of traditions about the sanctity of Judaism’s holiest of places. In the book of Exodus, one type of oil is used to light the lamps and another oil is used to anoint the Tabernacle and make it inviolate. The Tabernacle became part of the First Temple so there was no need to anoint the Holy of Holies there. In the time of the First Temple, some considered the Temple to be inviolate. When the First Temple was destroyed, no aspect of the new Temple was anointed. In the 160s BCE, during the Antiochene persecution, some felt the need to explain how the Temple could have been violated. The author of Daniel 9 reinterpreted Jeremiah’s prophecies of the 70 years of exile to be 70 weeks of years so that everything that had befallen the Judeans was seen as part of God’s overarching plan. The complex issues of continuity/discontinuity between, and the violability/inviolability of the temples, underlie Dan. 9 and related texts.
Keywords: Book of Daniel; Hanukkah; Jeremian prophecies; continuity/discontinuity; dept.jst; oil; peer-reviewed; temples

The failure of Poseidon, 'Averter of Disaster' and the mythical geography of Isaiah 23:1-14 - Scolnic, B. (Acta Antiqua Academiae Scientiarum Hungaricae, 2024)
The nostos, the return home in Greek mythology, is most often a journey over the sea, and it is the god Poseidon who rules the sea, both ensuring the safe passage of fishermen and sailors and causing disasters to individuals like Ajax son of Oileus, sometimes through obstacles like his daughter Charybdis. Most famously, he uses his power to hinder the nostos of Odysseus, all the while knowing he cannot prevent him from reaching home. This example illustrates how a god who may once have been the most powerful deity can no longer control ultimate results. As his power declines over the centuries, that of Zeus increases. It is also by sea that we see the ships in Isaiah 23, attempting to return to their homes in Sidon and Tyre on the eastern Mediterranean coast. In this Biblical passage from the eighth century BCE, the ships wail when they see that their seaport homes have been destroyed; there are no homes to which they can return. The great god of the Sea and the epichoric gods have failed to protect the cities which are considered their progeny. The Israelite prophet mocks their powerlessness and celebrates the power of his One God. There is no nostos, no homecoming for ships because they no longer have homes. Just as Poseidon could not prevent Odysseus from his nostos, the so-called Averter of Disaster has not prevented the disaster that has befallen his children. © 2023 Akadémiai Kiadó, Budapest.
Keywords: Biblical-Mythological Inter-Connections; Odyssey; Poseidon; dept.jst; nostos; peer-reviewed

Ἀντίπατρος ἀδελφιδοῦς: Was Antipatros son of Epigonos of Telmessos the “Nephew” of Antiochos III? - Scolnic, B. (Dialogues d'Histoire Ancienne, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.jst; peer-reviewed

When did the future Antiochos iv arrive in Athens? - Scolnic, B. (Hesperia, 2014)
The mention of an Antiochos in an Athenian inscription, I 7453, which dates to 178/7 b.c., has led scholars to accept that the future Antiochos IV lived in Athens from 178 to 175, and was not just present in the city in 175, as a statement by Appian seems to indicate. A reevaluation of the evidence calls into question both this extended sojourn and the identification of the Antiochos in the inscription, inviting us to reconsider the circumstances and the chronology of events surrounding the accession of Antiochos IV. © The American School of Classical Studies at Athens.
1 citations (Crossref) [2023-10-31]
Keywords: dept.jst

Heliodorus and the Assassination of Seleucus IV according to Dan 11:20 and 2 Macc 3 - Scolnic, B. (Journal of Ancient Judaism, 2016)
The impetus for the assassination of Seleucus IV in 175 B. C. E. is commonly associated with his robbing the temples and oppressing the peoples of the Seleucid kingdom in order to pay tribute to Rome according to the Treaty of Apamea. Reconsideration of the relevant evidence – especially Dan 11:20 and 2 Macc 3, with attention to a passage from Appian, inscriptions from Delos, the Heliodorus stele and the Ptolemaios dossier – suggests another explanation for these events. If Seleucus robbed the temples to finance his “royal splendor,” it is possible that Heliodorus and others tasked with taxing the kingdom may have objected to his controversial policies and taken action against him because of them. © 2016 [2017] Vandenhoeck & Ruprecht GmbH & Co. KG, Göttingen
0 citations (Crossref) [2023-10-31]
Keywords: dept.jst

Is Daniel 11:1-19 based on a ptolemaic narrative? - Scolnic, Benjamin (Journal for The Study of Judaism, 2014)
Daniel 11 is considered an exceptional Biblical text because of its interest in and accuracy about historical and political events in the Hellenistic world. A recent theory suggests that the author was a former Seleucid scribe; another theory posits the use of a Ptolemaic propaganda document. The approach here will be inductive, reading out from the text to adduce evidence that the author of Daniel 11 either used or reflected the attitudes of Ptolemaic narrative, not necessarily because he was pro-Ptolemaic but because it suited his anti-Antiochene purpose. © Koninklijke Brill NV, Leiden, The Netherlands.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-586-778-649-478 tex.type: [object Object]
Keywords: Bible; Daniel; Maccabean; Source criticism; dept.jst

Antiochus IV as the scorned prince in dan 11:21 - Scolnic, Benjamin (Vetus Testamentum, 2012)
While most English translations render nbzh in Dan 11:21 as "contemptible, vile, despicable," closer examination will demonstrate that this Biblical Hebrew word should be translated as "spurned, scorned, rejected." Once one understands Dan 11:21 accordingly, other ancient sources can be brought to show that this verse states, in its own thinly-veiled code, that before his rise to power, Antiochus IV, son of the late king Antiochus III and brother of the current king Seleucus IV, had been scorned and had not been given appropriate royal honors. This verse should be seen as another element in the evaluation of Dan 11 as an accurate and important historical source for the events surrounding the rise and rule of Antiochus IV. © 2012 by Koninklijke Brill N.V., Leiden, The Netherlands.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-577-169-045-737 tex.type: [object Object]
Keywords: Daniel; Hebrew Bible; Old Testament; dept.jst; translation